Nano composite material based on waste polyester resource utilization as well as preparation and application of nano composite material

By synthesizing MOF structures in situ in PET matrix, the problems of low economic benefits and poor composite performance in PET resource recycling were solved, and PET@MOF nanocomposites with excellent performance were prepared, which are suitable for friction nanopower generation and wearable self-drive equipment.

CN120535928APending Publication Date: 2025-08-26ZHEJIANG UNIV OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510934891.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-08
Publication Date
2025-08-26

AI Technical Summary

Technical Problem

The existing PET resource recycling technology has problems with low economic benefits and poor composite performance of MOF materials and polymers, and it is difficult to achieve efficient and concise functional composite of waste PET resource utilization and MOF materials.

Method used

By synthesizing the MOF structure in situ after controllable degradation of discarded PET, PET@MOF nanocomposite was prepared, and betaine catalyzed partial degradation of PET to form terephthalic acid as the ligand of MOF material, forming strong coordination bond binding, and achieving uniform growth of MOF inside the PET matrix.

Benefits of technology

The uniform dispersion of MOF materials in the PET matrix is ​​achieved, which significantly improves the interface bonding force and triboelectric properties of the composite material, simplifies the preparation process, is suitable for industrial production, and expands the high-value utilization of waste PET.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120535928A_ABST
    Figure CN120535928A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of waste utilization, and particularly relates to a nano composite material based on waste polyester resource utilization as well as preparation and application of the nano composite material. The preparation method comprises the following steps: firstly, dissolving metal salt in an organic solvent, and adjusting the solution to be acidic to obtain a metal salt precursor solution; adding the PET powder and betaine into alcohol, uniformly mixing, and carrying out incomplete degradation reaction in a heating state to obtain a mixed solution of the organic ligand and PET; after the mixed solution is cooled, alkali is added, and a prepared solution is obtained; and finally, fully mixing the prepared solution with the metal salt precursor solution, and reacting to obtain the composite material. According to the invention, the PET degradation degree is precisely regulated and controlled, and a metal-organic framework nano structure is constructed in situ, so that the prepared nano composite material has better electrical performance compared with a traditional friction generator material, and has potential application value in the field of wearable energy collection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of waste utilization, and in particular relates to a nano-composite material based on resource utilization of waste polyester and its preparation and application. Background Art

[0002] Polyethylene terephthalate (PET) has excellent chemical stability, good mechanical properties and low production cost, so it is widely used in many fields such as beverage bottles, packaging materials, textile fibers, etc. However, due to the difficulty of PET material degradation, the accumulation of a large amount of waste PET every year causes serious environmental pollution and resource waste. There is an urgent need to develop efficient and economical methods for the recycling of waste PET resources. Currently, PET resource recovery technologies mainly include physical recovery and chemical recovery. Physical recovery mainly involves sorting, cleaning, crushing and reprocessing waste PET. Although the process is simple, the product quality decreases significantly with the increase in the number of recycling times, and its application scope is limited. The chemical recovery method mainly depolymerizes PET into monomers or oligomers through catalytic degradation for re-synthesis, but there are problems such as complex process, low catalytic efficiency, high cost and difficulty in accurately controlling product quality, which limits its industrial-scale application. Therefore, the development of a new resource recovery technology that can effectively improve the economic benefits of waste PET recycling, simplify the process flow and has broad application prospects has become a key technical problem that needs to be solved in this field.

[0003] Metal-organic frameworks (MOFs), a new type of porous crystalline material, have recently shown promising applications in catalysis, gas storage, sensing, and energy conversion due to their large surface area and highly tunable structure and functionality. However, because MOFs are typically granular powders with poor mechanical properties, they often require composite materials with substrates with specific mechanical properties to meet the demands of device fabrication and scalable applications. Existing methods for composite MOFs with polymer substrates are complex and difficult to meet the diverse needs of practical applications.

[0004] Therefore, how to effectively combine the resource utilization of waste PET with the functional composite of MOF materials through a simple and efficient method to prepare a composite material with excellent performance and industrial prospects has become one of the important research hotspots in this field. Summary of the Invention

[0005] The present invention aims to overcome the low economic benefits of existing waste PET recycling and the poor performance of traditional metal-organic framework (MOF) and polymer composites. By proposing a nanocomposite material based on the resource utilization of waste polyester, its preparation method, and its application, these issues are overcome. This method involves controlled degradation of waste PET followed by in-situ synthesis of a MOF structure, producing a PET@MOF nanocomposite material with both excellent electrical and mechanical properties, achieving high-value utilization of waste PET.

[0006] To achieve the above-mentioned purpose, the present invention is implemented through the following technical solutions: A method for preparing a nanocomposite material based on resource utilization of waste polyester comprises the following steps: S1, dissolving a metal salt in an organic solvent and adjusting the pH value of the solution to acidic to obtain a metal salt precursor solution; S2, mixing waste polyethylene terephthalate powder with betaine and adding the mixture to an alcohol solvent, performing an incomplete degradation reaction under heating conditions, and preparing an organic ligand mixed solution containing a partial degradation product of PET; S3, after the mixed solution is cooled, alkali is added to obtain a preliminary solution; S4. Fully mix the preliminary solution and the metal salt precursor solution. After the reaction is completed, wash and dry the obtained insoluble matter to obtain a nanocomposite material based on the resource utilization of waste polyester.

[0007] The present invention prepares a PET@MOF nanocomposite material with excellent electrical properties by synthesizing a MOF structure in situ after controllable degradation of waste PET, thereby realizing high-value utilization of waste PET. The MOF material is formed by metal ions and organic ligands through coordination bonds, has a high specific surface area and an adjustable pore structure, and the porous framework in its structure can serve as an efficient charge capture site, effectively improving the surface charge density of the material. In addition, the electron donor-acceptor structure composed of metal nodes and organic ligands in the MOF material can effectively optimize the triboelectric sequence of the composite material, enhance the charge separation efficiency, and thus further improve the triboelectric output performance of the material. However, although pure MOF materials can be made into a film by pressing, they have poor mechanical properties, insufficient flexibility and are easy to break, making them difficult to directly and stably apply to triboelectric nano-power generation devices. Therefore, they usually need to be composited with a polymer matrix with good mechanical properties and flexibility to improve the overall performance and practicality of the material.

[0008] Currently, conventional MOF materials and polymers are typically composited through mechanical stirring, solution blending, or melt blending. These methods suffer from difficulties in uniformly dispersing MOF particles, insufficient interfacial bonding strength, and the need for additional dispersants, severely limiting the performance and stability of the composites. To address these issues, the present invention innovatively employs an in-situ synthesis method. Betaine is first used to catalyze the partial degradation of waste PET, forming a mixture of PET degradation products (terephthalic acid) and undegraded PET. This mixture is then mixed with a metal salt precursor solution for in-situ synthesis. During the reaction, the PET degradation products also act as ligands for the MOF material, resulting in uniform in-situ growth of the MOF within the PET matrix. Due to the strong coordination bonds formed between the MOF and the PET matrix, the composite's interfacial bonding strength and MOF particle dispersion are significantly enhanced, resulting in a more uniform electron transport pathway and ultimately significantly improving the material's triboelectric performance. The catalyst in step S2 is betaine. Betaine effectively catalyzes the controlled, incomplete degradation of PET, producing terephthalic acid and other PET partial degradation products, facilitating the subsequent in-situ synthesis of MOF materials.

[0009] Furthermore, the temperature of the incomplete degradation reaction in step S2 is 150-180°C, preferably 160°C.

[0010] Furthermore, the duration of the incomplete degradation reaction in step S2 is 6 to 9 hours, preferably 6 hours. By regulating the reaction temperature and time, the degree of PET degradation and product composition can be precisely controlled, thereby optimizing the effect of the subsequent in situ synthesis of MOF.

[0011] Furthermore, the alcohol solvent in step S2 is ethylene glycol. Ethylene glycol not only serves as a good reaction solvent, but also effectively promotes the moderate degradation of PET and improves product uniformity.

[0012] Furthermore, the organic solvent in step S1 is N,N-dimethylformamide (DMF). DMF can dissolve the metal salt precursor well and maintain good solution stability, which helps the subsequent reaction proceed smoothly.

[0013] Furthermore, the metal salt in step S1 includes one or both of zirconium chloride and zirconium nitrate. Using zirconium salts as precursors can synthesize MOF materials with higher structural stability and superior electrical properties. Among them, the UiO-66 type MOF, composed of zirconium oxide clusters and terephthalic acid ligands, exhibits excellent mechanical and electrical properties.

[0014] Furthermore, in step S4, the reaction temperature is 80-110°C, and the reaction time is 24-30 hours. The preferred reaction condition is 80°C for 24 hours, which enables the MOF material to grow uniformly within the PET matrix and achieves good interfacial coordination and bonding, thereby significantly improving the overall performance of the composite material.

[0015] Furthermore, the waste polyethylene terephthalate powder in step S1 is obtained by washing and crushing waste PET materials. While chemical recycling of waste PET plastics is typically complex and costly, the present invention employs a simple pretreatment process, a wide range of raw materials, and low cost, significantly expanding the economic value and practical application prospects of waste PET resource utilization.

[0016] The present invention also discloses a triboelectric material, which is prepared by the above-mentioned method for preparing the nanocomposite material based on resource utilization of waste polyester.

[0017] This invention also discloses the application of the aforementioned triboelectric material in a triboelectric nanogenerator (TENG). Compared to traditional electromagnetic generators, TENGs offer high voltage and low current, making them suitable for capturing low-frequency, micro-mechanical energy (such as human motion and water flow). The performance of the core triboelectric layer directly determines the charge density and device lifespan. The PET@MOF nanocomposite prepared in this invention effectively fulfills this role.

[0018] Therefore, the present invention has the following beneficial effects: (1) The present invention creatively couples the partial degradation reaction of waste PET with the in-situ synthesis of MOF materials, achieving uniform dispersion of MOF materials in the PET matrix, forming a composite material in one step, and realizing the high-value conversion of waste.

[0019] (2) The method of the present invention adopts a one-pot process, which simplifies the material preparation process, saves process steps and production costs, and is suitable for industrial-scale production.

[0020] (3) The present invention effectively realizes the high added value conversion of waste PET materials and provides a new resource utilization approach; the prepared PET@MOF nanocomposite material has excellent performance and broad application prospects, especially in the fields of triboelectric nanopower generation and wearable self-driving devices, and has good industrialization potential and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 XRD patterns of the PET@MOF composite material prepared in Example 1 of the present invention and standard UIO-66 and PET powders.

[0022] Figure 2 This is the SEM image of the PET@MOF composite material prepared in Example 1 of the present invention.

[0023] Figure 3 XPS spectra of the PET@MOF composite material prepared in Example 1 of the present invention and standard UIO-66.

[0024] Figure 4 XRD patterns of the PET@MOF composite materials prepared in Examples 1 to 3 of the present invention.

[0025] Figure 5 This is the XRD pattern of the PET@MOF composite material prepared in Example 4 of the present invention.

[0026] Figure 6 This is the XRD pattern of the PET@MOF composite material prepared in Example 5 of the present invention.

[0027] Figure 7 This is the XRD pattern of the sample prepared in Comparative Example 1.

[0028] Figure 8 This is the FTIR spectrum of the sample prepared in Comparative Example 2.

[0029] Figure 9 This is a performance comparison chart of the PET@MOF composite material prepared in Example 1 and commercial PET.

[0030] Figure 10 This is a voltage test comparison chart of the PET@MOF composite material prepared in Example 4 and Comparative Example 3. DETAILED DESCRIPTION

[0031] The present invention will be further described below with reference to specific embodiments. Those skilled in the art will be able to implement the present invention based on these descriptions. Furthermore, the embodiments of the present invention described below generally represent only a portion of the present invention, rather than all of the embodiments. Therefore, all other embodiments derived by those skilled in the art based on the embodiments of the present invention without inventive effort should fall within the scope of protection of the present invention.

[0032] Embodiment 1: (1) Weigh 0.01 mol of zirconium tetrachloride and add it to a mixed solution of 10 mL of DMF, 10 mL of deionized water, and 2 mL of hydrochloric acid. The pH of the solution is 3. Dissolve it by ultrasonication for 5 min to obtain a metal salt precursor solution.

[0033] (2) Take 4 g of PET powder and 0.2 g of betaine, mix them evenly, and add them to 16 g of ethylene glycol solvent. Raise the temperature to 160 °C and react by magnetic stirring. The reaction time is 6 h and the stirring rate is 400 r / min to obtain a mixed solution.

[0034] (3) Lower the temperature of the mixed solution to 80 °C, add 0.02 mol NaOH, and react for 10 min to completely dissolve the NaOH to obtain a preliminary solution.

[0035] (4) The prepared solution was fully mixed with the metal salt precursor solution, and the reaction was carried out at 80 °C for 24 h to obtain the product. The insoluble matter was washed with ethanol for 3 times to eliminate impurities in the preparation process, and then the PET@MOF composite material was obtained by drying.

[0036] Example 2: (1) Weigh 0.005 mol of zirconium tetrachloride and add it to a mixed solution of 10 mL of DMF, 10 mL of deionized water, and 2 mL of hydrochloric acid. The pH of the solution is 3. Dissolve it by ultrasonication for 5 min to obtain a metal salt precursor solution.

[0037] (2) Take 4 g of PET powder and 0.2 g of betaine, mix them evenly, and add them to 16 g of ethylene glycol solvent. Raise the temperature to 160 °C and react by magnetic stirring. The reaction time is 6 h and the stirring rate is 400 r / min to obtain a mixed solution.

[0038] (3) Lower the temperature of the mixed solution to 80 °C, add 0.02 mol NaOH, and react for 10 min to completely dissolve the NaOH to obtain a preliminary solution.

[0039] (4) The prepared solution was fully mixed with the metal salt precursor solution, and the reaction was carried out at 80 °C for 24 h to obtain the product. The insoluble matter was washed with ethanol for 3 times to eliminate impurities in the preparation process, and then the PET@MOF composite material was obtained by drying.

[0040] Example 3: (1) Weigh 0.0025 mol of zirconium tetrachloride and add it to a mixed solution of 10 mL of DMF, 10 mL of deionized water, and 2 mL of hydrochloric acid. The pH of the solution is 3. Dissolve it by ultrasonication for 5 min to obtain a metal salt precursor solution.

[0041] (2) Take 4 g of PET powder and 0.2 g of betaine, mix them evenly, and add them to 16 g of ethylene glycol solvent. Raise the temperature to 160 °C and react by magnetic stirring. The reaction time is 6 h and the stirring rate is 400 r / min to obtain a mixed solution.

[0042] (3) Lower the temperature of the mixed solution to 80 °C, add 0.02 mol NaOH, and react for 10 min to completely dissolve the NaOH to obtain a preliminary solution.

[0043] (4) The prepared solution was fully mixed with the metal salt precursor solution, and the reaction was carried out at 80 °C for 24 h to obtain the product. The insoluble matter was washed with ethanol for 3 times to eliminate impurities in the preparation process, and then the PET@MOF composite material was obtained by drying.

[0044] Embodiment 4: (1) Weigh 0.01 mol of zirconium nitrate and add it to a mixed solution of 10 mL of DMF, 10 mL of deionized water, and 2 mL of hydrochloric acid. The pH of the solution is 3. Dissolve it by ultrasonication for 5 min to obtain a metal salt precursor solution.

[0045] (2) Take 4 g of PET powder and 0.2 g of betaine, mix them evenly, and add them to 16 g of ethylene glycol solvent. Raise the temperature to 150 °C and react by magnetic stirring. The reaction time is 9 h and the stirring rate is 400 r / min to obtain a mixed solution.

[0046] (3) Lower the temperature of the mixed solution to 80 °C, add 0.02 mol NaOH, and react for 10 min to completely dissolve the NaOH to obtain a preliminary solution.

[0047] (4) The prepared solution was fully mixed with the metal salt precursor solution, and the reaction was carried out at 110 °C for 24 h to obtain the product. The insoluble matter was washed with ethanol for 3 times to eliminate impurities in the preparation process, and then the PET@MOF composite material was obtained by drying.

[0048] Example 5: (1) Weigh 0.01 mol of zirconium nitrate and add it to a mixed solution of 10 mL of DMF, 10 mL of deionized water, and 2 mL of hydrochloric acid. The pH of the solution is 3. Dissolve it by ultrasonication for 5 min to obtain a metal salt precursor solution.

[0049] (2) Take 4 g of PET powder and 0.2 g of betaine, mix them evenly, and add them to 16 g of ethylene glycol solvent. Raise the temperature to 180°C and react by magnetic stirring for 6 h at a stirring rate of 400 r / min to obtain a mixed solution.

[0050] (3) Lower the temperature of the mixed solution to 80 °C, add 0.02 mol NaOH, and react for 10 min to completely dissolve the NaOH to obtain a preliminary solution.

[0051] (4) The prepared solution was fully mixed with the metal salt precursor solution, and the reaction was carried out at 80 °C for 30 h to obtain the product. The insoluble matter was washed with ethanol for 3 times to eliminate impurities in the preparation process, and then the PET@MOF composite material was obtained by drying.

[0052] Comparative Example 1: (1) Weigh 0.01 mol of zirconium tetrachloride and add it to a mixed solution of 10 mL of DMF, 10 mL of deionized water, and 2 mL of hydrochloric acid. The pH of the solution is 3. Dissolve it by ultrasonication for 5 min to obtain a metal salt precursor solution.

[0053] (2) Take 4 g of PET powder and 0.2 g of betaine, mix them evenly, and add them to 16 g of ethylene glycol solvent. Raise the temperature to 160 °C and react by magnetic stirring. The reaction time is 12 h and the stirring rate is 400 r / min to obtain a mixed solution.

[0054] (3) Lower the temperature of the mixed solution to 80 °C, add 0.02 mol NaOH, and react for 10 min to completely dissolve the NaOH to obtain a preliminary solution.

[0055] (4) The prepared solution was fully mixed with the metal salt precursor solution, and the reaction was carried out at 80 °C for 24 h to obtain the product. The insoluble matter was washed with ethanol for 3 times to eliminate impurities in the preparation process, and then the comparative material 1 was obtained by drying.

[0056] Comparative Example 2: (1) Mix 10 mL of DMF, 10 mL of deionized water, and 2 mL of hydrochloric acid. The pH of the solution is 3. Ultrasonication time is 5 min to obtain a comparative solution.

[0057] (2) Take 4 g of PET powder and 0.2 g of betaine, mix them evenly, and add them to 16 g of ethylene glycol solvent. Raise the temperature to 160 °C and react by magnetic stirring. The reaction time is 6 h and the stirring rate is 400 r / min to obtain a mixed solution.

[0058] (3) Lower the temperature of the mixed solution to 80 °C, add 0.02 mol NaOH, and react for 10 min to completely dissolve the NaOH to obtain a preliminary solution.

[0059] (4) The preparative solution and the reference solution were fully mixed and reacted at 80 °C for 24 h to obtain the product. The insoluble matter was washed with ethanol for 3 times to eliminate impurities in the preparation process, and then dried to obtain reference material 2.

[0060] Comparative Example 3: UiO-66 was melt-mixed with PET, with the PET content being approximately 10%, to obtain comparative material 3.

[0061] like Figure 1 As shown in the XRD pattern, the composite material shows characteristic peaks of PET and UIO-66; Figure 2 The presence of zirconium can also be clearly seen in the EDS spectrum of the SEM shown; Figure 3 The XPS spectrum shown is identical to that of UIO-66 synthesized by the standard method, proving the successful synthesis of PET@MOF materials. Figure 4 As shown, by adjusting the amount of the added metal salt solution, the proportion of MOF in the resulting composite material can be adjusted. Figure 7 As shown, in Comparative Example 1, due to the long reaction time, the degree of PET degradation was too high, and the PET content in the system was very low, so the XRD showed that the peaks were basically the characteristic peaks of UIO-66. Figure 8 As shown, the PET material without adding metal precursor did not undergo obvious changes in properties after the above steps, indicating that the properties of PET in the composite material did not change.

[0062] The performance tests of the materials obtained in the examples and comparative examples were carried out, and the test methods and test setting conditions were as follows: The resulting composite material was melt-pressed using a fully automatic sheet press with a dwell time of 2 minutes, a temperature of 270°C, and a full pressing time of 8 minutes. The material was then formed into a 1 x 1 cm² film with a thickness of 0.1 mm. Triboelectric properties were tested using a linear motor. The TENG operated in contact-separation mode, with the electrode motion controlled by a linear motor (LinMot E1100, LinMot, Switzerland) with a cycle frequency of once every 3 seconds and an acceleration of 1 m / s². Open-circuit voltage and short-circuit current were measured using a programmable electrometer (Keithley Model 6514, USA) and a data acquisition system (Keithley Model DMM6510, USA). All experiments were conducted under controlled environmental conditions, with room temperature and humidity maintained at approximately 50%. The test results are shown in Table 1.

[0063] Table 1: Electrical performance test results of embodiments and comparative examples.

[0064]

[0065] like Figure 9 、 10 As shown, the composite material obtained by converting waste PET into a high-value material exhibits output performance improvements of at least 0.5-1 times that of commercial PET. Comparative Example 1 produced almost pure MOF material (UIO-66), which could not be made into a film for further testing. Comparative Example 2 produced pure PET material with electrical properties close to those of commercial PET. Comparative Example 3, which did not employ in-situ synthesis but instead used a traditional physical mixing method, exhibited even poorer performance than the examples.

[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a nanocomposite material based on resource utilization of waste polyester, characterized in that: The steps include: S1, dissolving a metal salt in an organic solvent and adjusting the pH value of the solution to acidic to obtain a metal salt precursor solution; S2, mixing waste polyethylene terephthalate powder with betaine and adding the mixture to an alcohol solvent, performing an incomplete degradation reaction under heating conditions, and preparing an organic ligand mixed solution containing a partial degradation product of PET; S3, after the mixed solution is cooled, alkali is added to obtain a preliminary solution; S4. Fully mix the preliminary solution and the metal salt precursor solution. After the reaction is completed, wash and dry the obtained insoluble matter to obtain a nanocomposite material based on the resource utilization of waste polyester.

2. The method for preparing a nanocomposite material based on resource utilization of waste polyester according to claim 1, characterized in that: In step S2, the reaction temperature is 150-180°C.

3. The method for preparing a nanocomposite material based on resource utilization of waste polyester according to claim 2, characterized in that: In step S2, the reaction time is 6 to 9 h.

4. The method for preparing a nanocomposite material based on resource utilization of waste polyester according to claim 1, characterized in that: The alcohol in step S2 is ethylene glycol.

5. The method for preparing a nanocomposite material based on resource utilization of waste polyester according to claim 1, characterized in that: The organic solvent in step S1 is N,N-dimethylformamide.

6. The method for preparing a nanocomposite material based on resource utilization of waste polyester according to claim 1, characterized in that: In step S1, the metal salt includes one or both of zirconium chloride and zirconium nitrate.

7. The method for preparing a nanocomposite material based on resource utilization of waste polyester according to claim 1, characterized in that: In step S4, the reaction temperature is 80-110° C., and the reaction time is 24-30 h.

8. The method for preparing a nanocomposite material based on resource utilization of waste polyester according to claim 1, characterized in that: In step S1, waste polyethylene terephthalate powder is obtained by washing and crushing waste PET material.

9. A triboelectric material, characterized in that: The nanocomposite material is prepared by the method for preparing the nanocomposite material based on resource utilization of waste polyester as described in any one of claims 1 to 8.

10. Use of the triboelectric material according to claim 9 in preparing a triboelectric nanogenerator.